The Reinforcement of Pesantren as Harmonization Agent of Religious Life in Pesantren “AL-FATAH” Singkawang, West Kalimantan - Muhtifah, Lailial (Jurnal Pendidikan Islam, 2016)
This article is to explore the reinforcement of Pesantren as harmonization agent of religious life, the foundation, strategies, procedures, and the assessment process of harmonization in pesantren "AL-FATAH" Singkawang West Kalimantan. The result of the study discovered that harmonization of religious life was based on the philosophical foundation of Islamic values (Islamic brotherhood/ukhuwwah Islamiyah, crossed-marriage, and collective system/jama’ah), foundation of national perspectives (Pancasila, the 1945 Constitution, NKRI, and Bhineka Tunggal Ika) and theoretical foundation (Islamic education, social culture, character education and the theory of conflict). Strengthening the strategy of harmonization through the achievement of the objectives, planning, the realization of activity in the form of concrete action, the existence of material, media, sequences and well-managed steps. Procedures of harmonization was applied through approach of method and technique, as reinforcement of pesantren as the harmonization agent of religions life. The assessment process of harmonization has not been carried out properly. The foundations, strategies, procedures and process of assessment have an impact on the emergence of P3AHKB culture and its implementation model. P3AHKB culture is the growth and the development of religious/spiritual values, honesty, responsibility, ukhuwwah Islamiyah, cooperation, empathy, social solidarity, respect, love, protect each other, get used to the language of the sunnah, keeping ethics, the formation of security culture, and rising prosperity with its business units and BMT. The implementation model is named "MI-P3AHKB tree."